Analisis Strategi Komunikasi Pemasaran Digital dalam Kegiatan Pemasaran Klub Olahraga - Damayanti, Ria; Sari, Yunita; Prasetya, Hendri (Jurnal Dinamika Ilmu Komunikasi, 2025)
XYZ is a sports club specializing in swimming and water polo training, primarily focusing on developing young athletes. In the digital era, the club utilizes social media as its main platform to promote services and enhance brand visibility among the public. This study aims to analyze the digital marketing communication strategies implemented by XYZ Sports Club and explore ways to optimize their effectiveness. The research adopts a post-positivist paradigm with a qualitative descriptive approach using a case study method. Data were collected through in-depth interviews with club managers, coaches, and members, as well as observation of digital activities across social media platforms. The findings reveal that XYZ has applied an integrated marketing communication framework encompassing five strategic principles: identification, individualization, interaction, integration, and integrity. However, the effectiveness of these strategies remains limited due to the absence of a structured customer feedback system and insufficient use of digital analytics. The study recommends strengthening data-driven evaluation mechanisms to enhance message personalization and improve the overall effectiveness of digital marketing communication in community sports organizations.